Inpatient Portals for Hospitalized Patients and Caregivers: A Systematic Review. Issue 6 (20th December 2017) - Kelly, Michelle M.; Coller, Ryan J.; Hoonakker, Peter L.T.
Abstract : Patient portals, web‐based personal health records linked to electronic health records (EHRs), provide patients access to their healthcare information and facilitate communication with providers. Growing evidence supports portal use in ambulatory settings; however, only recently have portals been used with hospitalized patients. Our objective was to review the literature evaluating the design, use, and impact of inpatient portals, which are patient portals designed to give hospitalized patients and caregivers inpatient EHR clinical information for the purpose of engaging them in hospital care. Literature was reviewed from 2006 to 2017 in PubMed, Web of Science, CINALPlus, Cochrane, and Scopus to identify English language studies evaluating patient portals, engagement, and inpatient care. Data were analyzed considering the following 3 themes: inpatient portal design, use and usability, and impact. Of 731 studies, 17 were included, 9 of which were published after 2015. Most studies were qualitative with small samples focusing on inpatient portal design; 1 nonrandomized trial was identified. Studies described hospitalized patients' and caregivers' information needs and design recommendations. Most patient and caregiver participants in included studies were interested in using an inpatient portal, used it when offered, and found it easy to use and/or useful. Evidence supporting the role of inpatient portals in improving patient and caregiver engagement, knowledge, communication, and care quality and safety is limited. Included studies indicated providers had concerns about using inpatient portals; however, the extent to which these concerns have been realized remains unclear. Inpatient portal research is emerging. Further investigation is needed to optimally design inpatient portals to maximize potential benefits for hospitalized patients and caregivers while minimizing unintended consequences for healthcare teams.